FENITIZATION HALOS IN PENCHENGA AND CHERNIGOVKA CARBONATITE MASSIFS: SIMILARITIES AND DIFFERENCES - Shnyukov, S.; Lazareva, I.; Nikanorova, Yu.; Morozenko, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Mineralogical, petrographic and geochemical features of carbonatites and fenitization halos of two linear carbonatite massifs, Penchenga (Yenisei Ridge) and Chernigovka (Pre-Azov Region), have been investigated. The purpose of the research was to identify and compare regularities of mineral association changes and major and trace elements behavior during the fenitization halo evolution over different host rocks (silicate and carbonate). To achieve this goal, we carried out three principal components of the laboratory and analytical study: petrographic investigation in thin sections to determine the mineral composition as well as the textural and structural features of rocks; X-ray fluorescence analysis to identify major and trace elements; interpretation of the data obtained. Our research produced the following results: (1) a similarity has been found in the direction of mineral association changes brought about by fenitization of different host rocks (silicate and carbonate) for both studied massifs (complete disappearance of such relict minerals as quartz, biotite and hornblende, and emergence of newly formed paragenesis: alkaline amphiboles, phlogopite, and calcite; an increase in apatite and pyrrhotite content, and the emergence of pyrochlore and titanite); (2) it has been found that in both cases, the main direction of changes in the contrast type host rocks caused by fenitization is the convergence of their mineral and chemical compositions; (3) according to their behavior during fenitization, the major and trace elements in each massif have been found to fall into three groups: lost, gained and redistributed; (4) the composition of these groups reflects a difference in the geochemical specialization of the massifs, which is also marked by the absence of nepheline rocks in the Penchenga massif in contrast to the Chernigovka massif; (5) similarities and differences in the Penchenga and Chernigovka carbonatite massifs have been revealed for the first time, and a common multiplicative geochemical zonation index has been constructed for both massifs to objectively show an increase in the level of contrast host rocks transformation. Using this index can enhance the efficiency of area selection and target evaluation.